Gut microbiota: An emerging therapeutic approach of herbal medicine for prevention of colorectal cancer - Ying, Hua-Zhong; Xie, Wei; Wang, Meng-Chuan; He, Jia-Qi; Zhang, Huan-Huan; Yu, Chen-Huan (Frontiers in Cellular and Infection Microbiology, 2022)
The gut dysbiosis has emerged as a prominent player in the pathogenesis and development of colorectal cancer (CRC), which in turn intensifies dysregulated gut microbiota composition and inflammation. Since most drugs are given orally, this dysbiosis directly and indirectly impinges the absorption and metabolism of drugs in the gastrointestinal tract, and subsequently affects the clinical outcome of patients with CRC. Herbal medicine, including the natural bioactive products, have been used traditionally for centuries and can be considered as novel medicinal sources for anticancer drug discovery. Due to their various structures and pharmacological effects, natural products have been found to improve microbiota composition, repair intestinal barrier and reduce inflammation in human and animal models of CRC. This review summarizes the chemo-preventive effects of extracts and/or compounds derived from natural herbs as the promising antineoplastic agents against CRC, and will provide innovative strategies to counteract dysregulated microbiota and improve the lives of CRC patients.